ECOLOGY IN THE SEVENTH-DAY ADVENTIST CHURCH - Legrants, Veren Julian; Pasuhuk, Suryanica Aristas (Klabat Theological Review, 2024)
This article discusses the ecological views of the Seventh-day Adventist Church (SDA) through a historical perspective from its early pioneers to the 21st century. The SDA church showed concern for the environment from the beginning, with an emphasis on vegetarian lifestyles, country/rural living, and human responsibility as stewards of God. The theological basis of environmental stewardship in the SDA church is based on the biblical concept of humanity’s role as the image and likeness of God. This article covers the ecological views of the SDA church in times of climate crisis, where the SDA church officially voices concern and proposes theological views regarding human responsibility in addressing climate change. In conclusion, the SDA church upholds the principle of environmental stewardship as an integral part of their religious life and practice and plays an active role in safeguarding and maintaining God’s creation. Keywords: SDA church, Ecology, Stewardship, Environment